Race, Culture, and Adoption: Lessons from Mississippi Band of Choctaw Indians v. Holyfield - Maldonado, Solangel (Columbia Journal of Gender and Law, 2008)
Jennie Bell, a member of the Mississippi Band of Choctaw Indians, a federally recognized tribe, was facing some difficult decisions. She was twenty-four years old, a single mother of two, and she was pregnant with twins by a man who was married to another woman and had two children of his own. Unemployed and not able to raise the twins herself, she turned to her family and other Choctaws on the reservation where she resided. Although her aunt offered to adopt one of the twins (the girl), no one was able or willing to take both children. Reluctant to separate the twins, Jennie, now seven months pregnant, continued her search for an adoptive family. Orrey Curtiss Holyfield, a Methodist minister, and his wife, Vivian Joan (“Joan”), had been trying to adopt for some time but had been repeatedly rejected by licensed adoption agencies because of their advanced age and Orrey’s poor health. At their attorney’s suggestion, they decided to pursue an independent adoption-one in which the birth parents place the child directly with the adoptive family with the help of an attorney, doctor, or clergy official rather than through a licensed agency. The Holyfields put the word out, and on Joan’s forty-fifth birthday, a member of their church and teacher on the Choctaw reservation called to ask if they were interested in adopting Choctaw twins. They immediately said yes. This Article uses the Supreme Court’s seminal opinion in Mississippi Band of Choctaw Indians v. Holyfield, best known for its affirmance of tribal sovereignty over adoptive placements of tribal children, to explore questions of racial and cultural identity and the meaning and role of race in adoptions. The Article proceeds in three parts. Part I focuses on the story behind the Supreme Court’s decision as recounted by Joan Holyfield and the attorneys who represented the Holyfields, the Mississippi Band of Choctaw Indians (the Tribe), and the children. Specifically, Part I explores how Jennie’s decision to place her children with the Holyfields, a non-tribal, Caucasian family, led to a four-year litigation involving the Mississippi state courts, the U.S. Supreme Court, and the Choctaw Tribal Court. It analyzes the Supreme Court’s interpretation of the Indian Child Welfare Act and its determination that tribal interests can trump individual tribal parents’ interests in selecting an adoptive family for their children. This Part also examines the Choctaw Tribal Court’s attempt to balance children’s best interests against tribal interests.